Green Budgeting for Sustainable Infrastructure: A Framework for Implementation in Islamic Boarding Schools (Pondok Pesantren) - Syaiful Muda'i; M. Burhanuddin Ubaidillah; Niken Ristianah; Juni Iswanto; M. Munir; Akhmat Fanani Ridho; Toha Ma'sum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study develops and proposes a Green Budgeting framework tailored for the implementation of environmentally friendly infrastructure in Islamic boarding schools (pondok pesantren). Green Budgeting, the integration of environmental criteria into financial planning and decision-making, is examined as a strategic tool to align pesantren expenditures with Islamic ecological values (hifdz al-bī'ah/environmental preservation) and sustainable development goals. Using a mixed-methods approach—combining qualitative case studies of pioneering pesantren with quantitative analysis of budget allocations and potential environmental impact—this research identifies key principles, processes, and challenges in adopting green fiscal practices. Findings reveal that successful Green Budgeting requires a value-driven reorientation linking maqashid sharia (higher objectives of Islamic law), lifecycle cost analysis, and participatory planning involving kyai, administrators, and santri (students). The study presents a phased model covering planning, procurement, monitoring, and reporting stages. It concludes that Green Budgeting can transform pesantren into institutional models of sustainability, ensuring that financial resources directly support ecological health, resource efficiency, and climate resilience, while fulfilling their educational and spiritual mission.